Reversibility of albuminuria and continuous positive airway pressure compliance in patients of obstructive sleep apnea syndrome. Issue 26 (June 2016) - Chen, Ning-Hung; Chou, Yu-Ting; Lee, Pei-Hsien; Lin, Shih-Wei; Chuang, Li-Pang; Lin, Yu-Sheng; Yang, Cheng-Ta
Abstract : Abstract: A positive correlation between albuminuria and severity of obstructive sleep apnea syndrome (OSAS) has been demonstrated, as indexed by urine albumin-to-creatinine ratios (UACRs). However, the effect of continuous positive airway pressure (CPAP) treatment on albuminuria in OSAS patients has not been established. Sixty subjects, with apnea-hypopnea indices >15 events per hour and no other diagnoses associated with albuminuria, underwent overnight polysomnography for sleep apnea and were examined for UACR at baseline and after 6 months of CPAP therapy. CPAP compliance rates were also recorded. Significant improvement in UACR was found in OSAS patients with good compliance to CPAP treatment after 6 months of therapy (baseline vs 6-month follow-up, 32.0 ± 9.5 vs 19.2 ± 6.5 mg/g, respectively, P = 0.007), whereas slight worsening in UACRs was noted in patients with poor compliance to CPAP treatment (baseline vs 6-month follow-up, respectively, 16.7 ± 4.4 vs 19.1 ± 6.3 mg/g, respectively, P = 0.39). Change in UACR was significant between poor compliance versus good compliance groups (2.4 ± 2.7 vs −12.8 ± 4.4 mg/g, respectively, t = 2.9, P = 0.005). A significant correlation between improvement in UACR and CPAP compliance rates was also noted (Spearman's correlation coefficient: −0.37, P = 0.007). Baseline UACR, good CPAP compliance, and body mass index were independent predictors of changes in UACR. Adequate CPAP treatment improves albuminuria in OSAS patients. In addition to monitoring CPAP adherence and subjective sleepiness, UACR may offer an objective physiological index of CPAP therapeutic effectiveness.